2001
DOI: 10.1046/j.1365-313x.2001.01096.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of drought tolerance by gene manipulation of 9‐cis‐epoxycarotenoid dioxygenase, a key enzyme in abscisic acid biosynthesis in Arabidopsis

Abstract: SummaryAbscisic acid (ABA), a plant hormone, is involved in responses to environmental stresses such as drought and high salinity, and is required for stress tolerance. ABA is synthesized de novo in response to dehydration. 9-cis-epoxycarotenoid dioxygenase (NCED) is thought to be a key enzyme in ABA biosynthesis. Here we demonstrate that the expression of an NCED gene of Arabidopsis, AtNCED3, is induced by drought stress and controls the level of endogenous ABA under drought-stressed conditions. Overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

66
916
0
19

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,170 publications
(1,001 citation statements)
references
References 39 publications
66
916
0
19
Order By: Relevance
“…Lastly, osmotic stress-induced starch degradation was abolished in the nced3 and aba2 mutants, but not in a mutant lacking AAO3 (Figures 6A and 6B; Supplemental Figure 10). Given that the major difference between these ABA biosynthetic mutants is their capacity to accumulate ABA in response to stress (Seo et al, 2000;Iuchi et al, 2001;Urano et al, 2009), our data suggest that the lack of stressinduced starch degradation in nced3 and aba2 was specifically caused by the complete absence of ABA accumulation. This is supported by the observation that the stress-induced transcriptional induction of BAM1 and AMY3 was substantially impaired in nced3, but not in aao3 ( Figure 6C).…”
Section: Aba Is the Primary Signal For Starch Degradation In Leaves Imentioning
confidence: 81%
See 2 more Smart Citations
“…Lastly, osmotic stress-induced starch degradation was abolished in the nced3 and aba2 mutants, but not in a mutant lacking AAO3 (Figures 6A and 6B; Supplemental Figure 10). Given that the major difference between these ABA biosynthetic mutants is their capacity to accumulate ABA in response to stress (Seo et al, 2000;Iuchi et al, 2001;Urano et al, 2009), our data suggest that the lack of stressinduced starch degradation in nced3 and aba2 was specifically caused by the complete absence of ABA accumulation. This is supported by the observation that the stress-induced transcriptional induction of BAM1 and AMY3 was substantially impaired in nced3, but not in aao3 ( Figure 6C).…”
Section: Aba Is the Primary Signal For Starch Degradation In Leaves Imentioning
confidence: 81%
“…The ABA-Deficient Mutants nced3 and aba2 Mimic the amy3 bam1 Phenotype under Osmotic Stress An essential step in stress-induced de novo ABA biosynthesis is the cleavage of epoxycarotenoids to produce xanthoxin (the first C15 intermediate) by the 9-cis EPOXYCAROTENOID DIOXYGE-NASE3 (NCED3) (Iuchi et al, 2001). This explains why the nced3-null mutant does not accumulate ABA in response to dehydration (Iuchi et al, 2001;Urano et al, 2009).…”
Section: Carbon Export To the Root And Osmolyte Accumulation During Omentioning
confidence: 99%
See 1 more Smart Citation
“…The cloning and characterization of maize Viviparous14, which encodes NCED1, led to identification of NCED as a rate-controlling enzyme in stress-induced de novo biosynthesis of ABA, particularly in leaf tissue Tan et al, 1997). Similar results were obtained from characterization of other ortholo-gous genes, PvNCED1 of bean (Phaseolus vulgaris; Qin and Zeevaart, 1999), VuNCED1 of cowpea (Vigna unguiculata; Iuchi et al, 2000), LeNCED1 of tomato (Solanum lycopersicum; Thompson et al, 2000a), and AtNCED3 of Arabidopsis (Arabidopsis thaliana; Iuchi et al, 2001). Stress-induced elevation of NCED transcript levels was observed to precede ABA accumulation (Qin and Zeevaart, 1999), and up-or down-regulation of the gene affected both ABA levels and drought sensitivity (Thompson et al, 2000b;Iuchi et al, 2001).…”
mentioning
confidence: 74%
“…Thus, it has been demonstrated that transgenic plants producing high levels of ABA display improved growth under drought stress than wild type (Iuchi et al, 2001;Qin and Zeevaart, 2002). Priming of ABA biosynthesis can be obtained by direct overexpression of 9-cis-epoxycarotenoid dioxygenase, a key enzyme in the biosynthetic pathway (Iuchi et al, 2001;Qin and Zeevaart, 2002), or through the use of chemicals that accelerate ABA accumulation (Jakab et al, 2005).…”
Section: Discussionmentioning
confidence: 99%